PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR SENI BUDAYA BIDANG SENI RUPA SISWA SMP NEGERI 3 PARIAMAN - LUCI DAHLIA Drs. Wisdiarman, M.Pd., Drs. Suib Awrus, M.Pd. (Serupa The Journal of Art Education, 2018)
This study aims to determine whether there is influence of the use of cooperative learning model type Example Non Example to the art and cultural art learning results in SMP Negeri 3 Pariaman. The type of research used in this research is quantitative research and using experimental method. The population in this study were all students of SMPN 3 Pariaman. The sample in this research is class VIII students with purposive sampling. Data were taken using t test. The findings in this study indicate that the students' learning outcomes using cooperative learning models of Example Non Example types differ significantly by using conventional learning models. This means the use of cooperative learning model type Example Non Example in learning is needed by every educator to improve student learning outcomes, especially art and cultural subjects in the field of fine arts SMPN 3 Pariaman.Keywords: Example Non Example, Learning Outcomes